KESIAPAN MAHASISWA PROGRAM STUDI TEKNIK SIPIL DAN BANGUNAN (D3) FT-UNP UNTUK MEMASUKI DUNIA KERJA DI BIDANG TEKNIK SIPIL - 584-590 , Zoni Azania Fernando (Universitas Negeri Padang, 2015)
Abstract This study is a quantitative descriptive research aimed at expressing readiness students of Civil Engineering and Building (PSTSB) class of 2011 to enter the world of work in the field of civil engineering, in terms of technical skills and soft skills. The study population was a student PSTSB (D3) of 2011 which is active in half of July to December 2014 amounted to 73 people. the samples were taken by simple random sampling technique with a number of students. Data for technical skills is taken from the value of 62 student. While the data obtained through a questionnaire soft skills. The results showed that in terms of technical skills, average the lowest scores were in the course of Building Construction and Draw 2 is 2.1032 with a category quite ready. average value is 3.2855 found in subjects Basic Concrete Structures, in the category of ready. In terms of soft skills, the percentage is the lowest degree of achievement of 61.244%, are in sub- indicators of entrepreneurial skills. The highest percentage of degree attainment is 82.065% contained in the sub- indicators of skills to work in team. Overall readiness of students in terms of soft skills, the average percentage of degree attainment is 75.112% and the category enough. Keywords: Readiness, Technical Skills, Soft Skills.